Projection of human immunodeficiency virus among high-risk groups in Malaysia - Mondal, Md. Nazrul Islam; Shitan, Mahendran (National Institute of Infectious Diseases, 2013)
Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) presents a serious healthcare threat to young individuals in Malaysia and worldwide. This study aimed to identify trends in HIV-related risk behaviors among recognized high-risk groups and to estimate HIV transmission up to the year 2015. Data and necessary information were obtained from the Ministry of Health Malaysia, published reports from the World Health Organization and United Nations Program on HIV/AIDS, and other articles. The Estimation and Projection Package was used to estimate HIV transmission. The results of the present study revealed that within the high-risk groups, intravenous drug users (IDUs) had the highest prevalence rate of HIV transmission, followed by patients with sexually transmitted infections (STIs), female sex workers (SWs), and men who have sex with men (MSM). Within these at-risk populations, patients with STIs have the highest prevalence of HIV, followed by IDUs, MSM, and SWs. If the transmission rate continues to increase, the situation will worsen; therefore, there is an urgent need for a comprehensive prevention program to control HIV transmission in Malaysia.